Standardization of AmukkiraiChooranam, a Traditional Herbal Preparation in Siddha System of Medicine - Vinotha, S.; Ira, T.; Sri Ranjani, S. (My University, 2015)
Introduction: Amukkirai chooranam (A. chooranam) is an important traditional herbal preparation and its main component is the root powder of Withania somnifera Dunal (Solanaceae). It is the best remedy for rheumatism, weakness, stress, sleeping disorders, gastric ulcer, anaemia, etc. Aims: The goal of this study was to standardize this traditional herbal preparation on the basis of qualitative and quantitative methods. Study Design: Experimental laboratory study on Phytochemical and Pharmacognostic investigations. Place and Duration of Study: The Phytochemical and pharmacognostic investigations were carried out at the Herbal Technology Section, Industrial Technology Institute (ITI), Colombo, Sri Lanka, between Jan 2012 to August 2012. Methodology: The A. chooranam was prepared according to the procedure given in Traditional Text. The preparation has been standardized on the basis of macroscopic and organoleptic characters, physicochemical properties, phytochemical screening, fluorescence analysis, and elemental analysis, aqueous and ethanol extractive values, TLC and HPLC fingerprint analysis. Data were analysed by statistical software - Statistical Package for Social Sciences (SPSS) version 17. Results: The present study reveals that the A. chooranam was light whitish brown in colour having characteristic odour with bitter taste and smooth texture. The moisture content at 105ºC in A. chooranam was found to be 9.12±0.10%. Analytical results showed total ash, water soluble, acid insoluble and sulfated ash values of 5.76±0.09%, 2.93±0.15%, 0.63±0.04% and 1.92±0.04% respectively. The percentage yields of cold and hot aqueous extractive values (15.02±0.46 & 30.82±1.09) were greater than the percentage yield of cold and hot ethanol extractive values (03.07±0.31 & 10.00±0.22) of A. chooranam. Heavy metal analysis revealed that their concentrations in A. chooranam were below the WHO/FDA permissible limits. Conclusion: A. chooranam exhibits a set of diagnostic characters, which will help to identify the standard preparation and build a monograph of the Siddha pharmacopeia of Sri Lanka.
Keywords: Amukkirai chooranam; chromatography; herbal preparation; quality control